What is the potential for replacing monocultures with mixed-species stands to enhance ecosystem services in boreal forests in Fennoscandia? - Huuskonen S (ELSEVIER, 2025)
The boreal forests of Fennoscandia are largely dominated by Norway spruce and Scots pine. Conifer monocultures have been favoured in forest management during the last decades. Recently, concern has risen that forests consisting of only one tree species could be vulnerable to biotic damage. Additionally, environmental and societal changes are placing new demands on forest utilization, thus shifting the focus to alternative forest management options providing a wider scale of ecosystem services. It has been proposed that mixed forests are better than monocultures with respect to biodiversity, risk management and recreational value. By synthesising research studies, we provide an overview of current knowledge on how to combine wood production and other ecosystem services in mixed boreal forests in Fennoscandia. We addressed the following questions in more detail: what are the effects of mixed forests on soil properties, understorey vegetation, biodiversity, wildlife, resistance to and resilience against damage, forest productivity and the multiple use of forests? Furthermore, what are the silvicultural possibilities for establishing and managing mixed forests?Based on this review, mixed forests appear to provide a higher output of most ecosystem goods and services, including higher biodiversity and improved risk management, soil properties and multiple-use values. The most serious challenge is the browsing by cervids, which damages sapling stands. There is potential to establish single-storied mixed forests with current regeneration methods and material. Further research is particularly needed on the silvicultural practices suited for mixed boreal forests.